PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWA PADA PT. MULIA SUKSES JAYA DI BOGOR - Ridwan, Muhammad; Muharomi, Ahmad (Kinerja, 2019)
Every company wants the goals set can be achieved in a timely manner. Therefore, it is necessary to have good management of human resources owned by a company. In this study to determine the effect of variables with the title "Effect of Work Compensation and Discipline on Employee Performance. This research was conducted on the employees of PT. Mulia Sukses Jaya with 30 respondents and using a saturated sampling technique so the sample used is all populations, namely 30. Analysis techniques using correlation and regression analysis and hypothesis testing t and f as well as the coefficient of determination R2 with data processing using SPSS26. Based on the results of data analysis from the test the value of t count 2,192> 2,052 t table. And the sig value of 0.037 <0.05 means that Ha is accepted and Ho is rejected then Compensation has a significant effect on Employee Performance. While work discipline has a value of 5.074> 2.052 t table and a sig value of 0.000 <0.05 which means that Work Discipline has a significant effect on Employee Performance. Based on the f test results the f value of 12.704> 3.35 f table value and the value of the significance level of 0.000 <0.05. With this, Ha is accepted and Ho is rejected, which means Compensation and Work Discipline together - positive and significant effect on Employee Performance at PT. Mulia Sukses Jaya. The coefficient of determination is 0.485 which means that compensation and work discipline have an effect of 48.5% on employee performance. The remaining 51.5% is influenced by other factors outside the variables of this study.